2022
DOI: 10.1155/2022/8669993
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Studies on the Mechanisms of Chinese Medicine Formula (Yiqi Jianpi Jiedu Formula) in the Treatment of Hepatocellular Carcinoma

Abstract: Objective. Traditional Chinese medicine (TCM) is an important part of the comprehensive treatment of hepatocellular carcinoma (HCC), and Chinese materia medica formulas with the effect of “Yiqi Jianpi” (replenishing qi and strengthening spleen) or “Jiedu” (removing toxicity) have been proved to be effective in treating HCC. However, mechanisms of these formulas in treating HCC remain unclear. In this paper, our goal is to explore the antitumor activity and its molecular mechanisms of Yiqi Jianpi Jiedu (YQJPJD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Several in vivo and in vitro experiments have shown that Chinese herbal formulas are based on invigorating qi, strengthening the spleen, tonifying the kidneys, and removing toxins and blood stasis. Therefore, TCM treatments considerably reduces proliferation, survival, and progression of HCC cells by regulating key signaling pathways such as PI3K/Akt, β-catenin, MAPK3, and RHOA[ 30 - 32 ]. SPXJ formula has been shown to stabilize tumors, improve patients’ quality of life, and resist recurrence and metastasis in the clinical treatment of liver cancer[ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo and in vitro experiments have shown that Chinese herbal formulas are based on invigorating qi, strengthening the spleen, tonifying the kidneys, and removing toxins and blood stasis. Therefore, TCM treatments considerably reduces proliferation, survival, and progression of HCC cells by regulating key signaling pathways such as PI3K/Akt, β-catenin, MAPK3, and RHOA[ 30 - 32 ]. SPXJ formula has been shown to stabilize tumors, improve patients’ quality of life, and resist recurrence and metastasis in the clinical treatment of liver cancer[ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al demonstrated that Huanglian Jiedu decoction, one of the most commonly used classic TCM formulae, could remarkably suppress HCC cells growth in vitro and vivo [ 9 ]. Wu et al showed that Yiqi Jianpi Jiedu formula exerts its anti-HCC effect of HCC by β-catenin, mitogen-activated protein kinase 3 (MAPK3), PI3K/AKT pathway and ras homolog family member A (RHOA) [ 10 ]. Liu et al demonstrated that astragalus membranaceus directly down-regulated MT1G through daidzein to promote ferroptosis of HCC cells and improved prognosis for HCC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%